Atypical Clinical Presentation of Isolated Extraocular Muscle Sarcoid. (24th December 2012) - So, Wing Lung Alvin; Hardy, Thomas G.; McKelvie, Penelope
Abstract : A case of painless isolated extraocular muscle sarcoid and a literature review are presented. The atypical features in our case include a lack of overt inflammatory symptoms and signs, such as pain, ptosis, and diplopia. The presentation of minimal symptoms without improvement warrant a biopsy to establish the diagnosis and to administer appropriate treatment in order to prevent potential long-term complications from sarcoidosis.